SIRPα modulates microglial efferocytosis and neuroinflammation following experimental subarachnoid hemorrhage via the SHP1/STAT6 axis - Bingtao Zhang; Yan Zou; Qikai Tang; Zixuan Yuan; Kun Jiang; Zhaoxiang Zhang; Shujuan Chen; Qi Wu; Xiaoming Zhou; Xin Zhang (Journal of Neuroinflammation)
Abstract Subarachnoid hemorrhage induces extensive neuronal cell death, leading to the release of damage-associated molecular patterns (DAMPs). These DAMPs, along with hemoglobin and cell corpses, trigger localized inflammation. Signal regulatory protein alpha (SIRPα) plays a crucial role in efferocytosis by acting as a “don’t eat-me” signal, modulating inflammation and tissue homeostasis. However, the precise function and regulatory mechanisms of SIRPα in efferocytosis remain unclear. Proteomic analysis of cerebrospinal fluid (CSF) reveals that SIRPα levels are significantly elevated in the CSF of SAH patients and correlate with clinical outcomes. In vivo and in vitro studies show that microglial knockdown of SIRPα promotes efferocytosis and attenuates neuroinflammation following SAH. SIRPα inhibits efferocytosis by recruiting and phosphorylating SHP1 and SHP2 through phosphorylation of four tyrosine residues in its cytoplasmic domain, with SHP1 playing a particularly critical role. Mutation of these tyrosine residues to non-phosphorylatable alanine residues enhances efferocytosis and reduces neuroinflammation in vitro. RNA-seq analysis suggests that this mutation upregulates the expression of “eat-me” signals, MerTK and CD36, and identifies STAT6 as a key transcription factor involved in this process. In conclusion, SIRPα plays a central role in regulating microglia efferocytosis and neuroinflammation after SAH via the SHP1/STAT6 axis. Targeting this pathway may provide a promising therapeutic approach for SAH.